How to set up your own successful small scale industry - "Shukla, R. S." (New Delhi, 1993)
Today, Japan is known as the house of electronics. Anything that is Japanese is bound to be perfect. However, many of us can recall the Japanese toys, household goods, radios etc. Produced in the forties which were only cheap imitations. The goods were flimsy, component failure was endemic and the modelling superficial. In fact, the only thing consistent about their production was an international reputation of shoddy mimicry, such indeed were the products of a 5,000 year old society.
Keywords: Time and markets